SOSIALISASI COA KUARTET DAN EASY COA BAGI SISWA SMK BHAKTI NUSANTARA 666 CILEUNYI - Riani Tanjung; Mohamad Nurkamal Fauzan (Universitas Merdeka Madiun, 2025)
This community service program aims to enhance students' understanding of the Chart of Accounts (CoA) through educational innovation using CoA Quartet learning media and Easy CoA. SMK Bhakti Nusantara Cileunyi, located in Bandung Regency, West Java, is an educational institution offering an Accounting and Financial Institution program. Despite being equipped with various facilities and professional educators, students still face challenges in grasping basic accounting concepts, particularly the CoA. This is attributed to conventional teaching methods that are less interactive and fail to create engaging and inspiring learning experiences. To address these issues, we propose the use of CoA Quartet, an enjoyable educational card game, and Easy CoA, a technology-based application that helps students understand CoA more practically and comprehensively. The conclusion from the use of COA Quartet and Easy COA as learning media has proven effective in enhancing the understanding of SMK Bhakti Nusantara 666 Cileunyi students regarding the Chart of Accounts (CoA) material. This is evidenced by a significant increase in average scores and a significant decrease in score variation among students. This learning media is very good to be included in regular learning.